Modern trends in governance of state ownership relations - Umantsiv, Iurii; Lebedeva, Larysa; Mytrofanova, Anastasiia (Baltija Publishing, 2019)
Today, the diversity of functions of the state is objectively expanding, especially in the context of socially oriented economies of developed countries. Effctive governance of state property serves as a solid foundation for successful performance of the state functions. The chosen topic is of particular relevance in the context of Ukraine's transformational economy. The subject of research is the system of economic relations of state property. Methodology. In the course of the study, a general philosophical dialectical method was used to fid contradictions in the phenomena and sources of their development, such as the essence of state property and its contents. Common scientifi methods were also used: analysis and synthesis; comparative analysis; statistical methods for calculating the structure and dynamics of indicators of condition and development of state property. The overall system for assessing the socio-economic effiency of state property management was carried out on the basis of microeconomic indicators and macroeconomic indicators (indicators of economic and social effiency). The purpose of the paper is to reveal the trends of development of state ownership relations in the European countries as well as in Ukraine, in particular, the diffilties of the process of managing them, as well as to formulate possible ways to overcome such diffilties. Conclusions of the study. Today, the importance of the state as a public institute is objectively increasing in the most economically developed countries. By succeeding in achieving positive institutional changes in ownership relations (creating favorable conditions for SMEs, developing market infrastructure, conducting moderate privatization of state property, transferring state-owned enterprises to market tracks, maintaining policies for protecting national interests, etc.) the grounds for economic growth and improvement of the social sphere in France and Poland were made. Though the conducted analysis showed that the development of state property in Ukraine is contradictory, it has the following problems: ambiguous character of privatization; low effiency of state property governance; insuffient effiency of work of enterprises with state ownership; institutional problems. Overall, the socio-economic effiency of state property governance in Ukraine needs improvement. Thus, the state policy of property governance should include, in particular, the following steps: development of a national model of governance, as well as strategies for the development of state property; organization of state property management entities; development of a system of criteria and indicators for assessing not only the economic but also the social effiency of state property governance.
Keywords: state property; role of state in economy; state corporate rights; socio-economic effiency; privatization